2021
DOI: 10.1002/slct.202100315
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Efficacy of Natural Ubiquinol Compared to Synthetic References – In Vitro Study

Abstract: There are many studies dealing with the oxidized form (Ubiquinone) of coenzyme Q10, but only a little of its reduced form (Ubiquinol). Two yeast-based Ubiquinols (UQH 2 _S, Sigma-Aldrich; UQH 2 _K, Kaneka) were investigated for in vitro antioxidant efficacy compared to synthetic antioxidants. The antioxidant efficacy of UQH2_S and UQH2_K by the 2,2-diphenyl-1picrylhydrazyl' (DPPH) assay as well as by the 2,2'-azino-bis(3ethylbenzthiazoline-6-sulfonic) acid' (ABTS) assay was almost identical (IC50 DPPH/ABTS 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The imbalance between production and accumulation of free radicals causes oxidative stress in human body, including the skin (Poljšak and Dahmane, 2012;Pizzino et al, 2017;Sudarikov et al, 2021). To either prevent these reactive species from formation or remove them before they can damage vital components of the skin cells, synthetic antioxidants such as α-tocopherol, butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) are commonly incorporated into skin care products (Hatwalne, 2012;Ácsová et al, 2021). However, BHA and BHT are under investigation due to concerns regarding their side effects, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance between production and accumulation of free radicals causes oxidative stress in human body, including the skin (Poljšak and Dahmane, 2012;Pizzino et al, 2017;Sudarikov et al, 2021). To either prevent these reactive species from formation or remove them before they can damage vital components of the skin cells, synthetic antioxidants such as α-tocopherol, butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) are commonly incorporated into skin care products (Hatwalne, 2012;Ácsová et al, 2021). However, BHA and BHT are under investigation due to concerns regarding their side effects, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Iron is one of the heavy metal ions present in atmospheric pollutant The reaction of oxygen with iron ions contributes to the production of ROS in the cytosol and all organelles of cells. Protection against iron toxicity is provided through the electron transfer and chelation of iron ions by antioxidants [25] what is specified as secondary antioxidant activity and can be determined by the FRAP method. Results depicted in Figure 3 shown that ASX-T and ASX-O at 5, 10, 15 and 40 μM have significantly higher ability (p < 0.05) to reduce Fe 3 + to Fe 2 + compared to AT.…”
Section: Ability Of Test Substance To Reduce Metal Ionsmentioning
confidence: 99%